Analysis of the Use of Waste Plastics Low-Density Polyethylene (LDPE) along with Bitumen in the Construction of Asphalt Pavement using the Marshall Test - Poudel, Dipika; Timsina, Dikshya; Poudel, Mansun; Acharya, Janam; Thapa, Prasidha; Khadka, Reeta (International Journal on Engineering Technology, 2024)
Plastic disposal is a significant problem as it is non-biodegradable and causes air pollution if burned. The utilization of waste plastics in road construction has gained attention due to environmental concerns and the need for sustainable development of infrastructure. This research investigates the performance waste plastics, low-density polyethylene (LDPE) and, in the asphalt road along with the bitumen based on the Marshall Stability Test. The Optimum bitumen content (OBC) is found to be 5.2%. Different concentrations of LDPE (8% and 10% by weight of bitumen) were used. The use of LDPE on the asphalt pavement has Marshall Stability and Marshall flow values in the usable range as specified in the specification criteria of the Standard Specification for Road and Bridge Works (SSRBW). Also, the use of waste plastics in the pavement reduces the cost and helps to promote an environmentally friendly approach to infrastructure development.